Assessment of the knowledge, Attitude and practice (KAP),of nurses regarding care of elderly patients (Tehran 1993). - mahboobeh- mohtashamy (Iran University of Medical Sciences, 1996)
The research was a descriptive study to assess knowledge, attitude and practice (kap) of nurses regarding care of elderly patients.   A total of 180 nurses working in medical, surgical and neurology units participated in this study. The tool was a 2 part questionnaire that the first part included demographic characteristics of the subjects like age, sex, marriage, education, past experience in nursing and experience on elderly units.   The second part posed 46 questions regarding assessment of knowledge and attitude towards elderly patient.   The subjects were asked 30 more questions in the form of check list to measure the quality of the care taking of elderly patients.   The results showed that 50% of the nurses had good knowledge about elderly patients and also there was an inverse correlation between their knowledge, age and years of service.   The data also revealed that 71% of nurses had positive attitude, 29% neutral and very low percentage had negative attitudes, also the fact that younger nurses were more positive than older ones. The analysis indicated that as for as the quality of nursing practice for elderly was concerned, 34% ranked good and 34% satisfactory. There was also on inverse correlation between quality of practice and years of service. The analysis also concluded that in spite of the fact that majority of nurses had good knowledge and attitude but minority had good practice in caring elderly patients.